Changes in physicochemical properties and digestive characteristics of yam (Dioscorea opposita Thunb.) powder under different processing conditions using principal component analysis. Issue 12 (10th September 2019) - Guan, Qianqian; Li, Hua; Qi, Yuting; Zhang, Wenlong; Liu, Lina; Qiu, Bin; Liu, Wei; Jia, Min; Xu, Tongcheng; Zong, Aizhen
Abstract: This study aimed to understand and establish changes in the physicochemical properties of yam powder with different processing methods, and select a suitable method for use in the development of hypoglycemic functional foods. Samples were dried using three methods, namely hot air drying, vacuum freeze drying, and microwave vacuum drying, and turned to powder using two smashing methods, namely ordinary smashing and superfine smashing (SS). Color changes, polarized light microscopy, differential scanning calorimetry, X-ray diffraction, polysaccharide dissolution rates, α-glucosidase inhibitory activities, glucose dialysis retardation indexes, and digestive characteristics were measured. The results showed that the drying method and the smashing method had significantly different effects on the physicochemical properties and digestion characteristics of the yam powder. Freeze-dried yam retained more nutrients, while SS increased the rapidly digestible starch content, reduced the digestible starch and resistant starch contents, and increased the polysaccharide dissolution rate in the yam powder samples. Six samples were compared using principal component analysis, with the highest composite score observed for the samples treated by freeze drying coupled with SS, followed by hot-air drying coupled with superfine smashing (HAO).